Pengaruh Kombinasi Media Tanam Terhadap Tanaman Timun Apel (Cucumis sp.) Pada Fase Pembibitan - Agustia, Putry Nabilah; Bayfurqon, Fawzy Muhammad; Agustini, Rika Yayu (JURNAL AGROPLASMA, 2024)
The determination of the application of planting media during seedling is a basic thing that needs to be known (Bayfurqon, 2019).  This study aims to determine the effect of the combination of planting media on the seeding of apple cucumber plants (Cucumis sp.) The experiment was carried out at  the screen house on Jalan Gang Histori, Kalijaya Hamlet 1 RT 003/RW 009 North Rengasdengklok Village, Rengasdengklok District, Karawang Regency starting from March 2024 – April 2024. The research method used was an experimental method using a single-factor Group Random Design (RAK) with 7 treatments that were repeated 4 (four) times, namely: m0 (soil), m1 (Cocopeat), m2 (husk charcoal), m3 (Cocopeat + cow manure), m4 (husk charcoal + cow manure), m5 (Cocopeat + cow manure + soil) and m6 (husk charcoal + cow manure + soil). The effect of the treatment was analyzed using the 5% F test, so to find out the best treatment, it was followed by the Duncan Multiple Range Test (DMRT) at the 5% level. The results showed that the combination of planting media had a real influence on the seeding of apple cucumbers (Cucumis sp.). The M0 (soil) treatment gave the best results in plant height (13.34 cm), stem diameter in M0 treatment (2.35 mm), number of leaves in M0 treatment (4.12 leaves), leaf area in M0 treatment (11.28 cm2), plant fresh weight in M0 treatment (1.29 g) and success percentage in M6 treatment (100.00%), but there was no significant difference in growth synchronicity. Keywords: cucumber apple, nursery, combination of planting media